Pengembangan Program Jembatan Penyeberangan Orang Menjadi Penyeberangan Mobil di Desa Sukatani - Eugenius Pradipto; Andreas Triwiyono (Universitas Serang Raya, 2018)
Human-crossing bridge development project in Sukatani Village, an underdeveloped area in Sukabumi Sub-district, West Java Province on 2013 was a program resulted from a collaborative work between Kementerian Negara Pembangunan Daerah Tertinggal (State Ministry for Development Acceleration in Underdeveloped Regions) and Lembaga Kerjasama Fakultas Teknik Universitas Gadjah Mada (Faculty of Engineering Cooperation Agency). In this program, Dinas Bina Marga dan Tata Ruang Provinsi Jawa Barat was involved as a technical supervisor. In this project, LKFT UGM’s role and function in carrying out the values of Tri Dharma Perguruan Tinggi were done through the implementation of a social participation model. This social participation model positioned the local community as an object of education and development. The project’s funding from Kementerian PDT was independently managed by Organisasi Masyarakat Sipil (Civil Society Organization). In managing the funding, a progress report scheme was implemented as control and education tool. The trust that was established among involved parties allowed some kind of coaching process to support a full role from the local society in the bridge development project. Finally, the project resulted in a high quality bridge that exceeded the project’s target and initial expectation from a human crossing bridge to a car crossing bridge. This escalation was able to raise the local society’s confidence and sense of belonging towards the bridge as their own hand work. Then on the next fiscal year of 2014, the local government further improved the bridge’s quality from a car crossing bridge into a heavy vehicle crossing bridge.